2022
DOI: 10.1039/d1ra08658h
|View full text |Cite
|
Sign up to set email alerts
|

Selenium nanoparticles inhibited H1N1 influenza virus-induced apoptosis by ROS-mediated signaling pathways

Abstract: SeNPs inhibited the apoptosis induced by H1N1 virus infection in MDCK cells by improving the level of GPx1. Our results suggest that SeNPs are an effective selenium source and a promising H1N1 influenza antiviral candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…The activity of GPX-1, a member of the GSH-Px family, was reduced in H 1 N 1 infected MDCK cells, and SeNPs treatment increased GPX-1 activity, consistent to a certain extent with findings reported by Liu et al In addition to its antioxidant effect, Se plays an important role in immune regulation in the form of selenoprotein. 43 Yao et al reported that Se supplementation could enhance GPX4 expression in T cells, increase follicular helper T cell numbers and promote antibody responses in immunized mice and young adults after influenza vaccination. 44 Nevertheless, the absorption, bio-transformation, and utilization of CS-SeNPs in mammalian cells remain poorly understood, warranting further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of GPX-1, a member of the GSH-Px family, was reduced in H 1 N 1 infected MDCK cells, and SeNPs treatment increased GPX-1 activity, consistent to a certain extent with findings reported by Liu et al In addition to its antioxidant effect, Se plays an important role in immune regulation in the form of selenoprotein. 43 Yao et al reported that Se supplementation could enhance GPX4 expression in T cells, increase follicular helper T cell numbers and promote antibody responses in immunized mice and young adults after influenza vaccination. 44 Nevertheless, the absorption, bio-transformation, and utilization of CS-SeNPs in mammalian cells remain poorly understood, warranting further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Liu et al reported that SeNPs could inhibit H 1 N 1 influenza virus-induced apoptosis by ROS-mediated signaling pathways. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Wang et al manifested that sodium selenite (SS) and (Se-Met) could reduce tertbutyl hydroperoxide (TBHP) induced oxidative stress, inhibited mitochondrial fission and apoptosis of nucleus pulposus cells (NPCs) (56). In vitro studies have shown that selenium supplementation can inhibit viral infection by increasing glutathione peroxidase 1 (Gpx1) activity and reducing reactive oxygen species (ROS) content, JNK phosphorylation levels (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Nano-Se of 200 nm was prepared from combining Na 2 SeO 3 (0.1 M) and vitamin C and verified for inhibition of influenza (H1N1) virus (Liu et al, 2022). Influenza A (H1N1) virus infection in humans not only leads to respiratory diseases but also occasionally causes severe lethal pneumonia and nervous system damage.…”
Section: Antiviral Properties Of Nano-sementioning
confidence: 99%
“…Madin-Darby canine kidney cell viability after treatment with Nano-Se@ZNV reached 72.7% from 62.2% cells treated with ZNV (Figure 5A). Furthermore, the RNA level of H1N1 after treatment with different groups (ZNV, Nano-Se, and Nano-Se@ZNV) was determined, and it indicated that the cells treated with Nano- (Liu et al, 2022).…”
Section: Antiviral Properties Of Nano-sementioning
confidence: 99%